Effect of 818A and 827N flocculants on seawater magnesia process - Petric, Nedjeljka (Kovine zlitine tehnologije, 1999)
Possibilities for the application of the anionic 818A flocculant (polyacrylamide) produced by the Dutch firm Hercules have been studied in order to increase the settling rate of magnesium hydroxide from sea water and to define the optimum conditions during the precipitation process. The efficiency of the 818A flocculant has been compared to the nonionic 827N flocculant. Examinations were carried out with different degrees of completeness of precipitation and with different quantities of the 818A flocculant. The dependence obtained was described by the appropriate analytical expression. The study has shown that the settling rate is higher during nonstoichiometric precipitation, i.e. precipitation when the quantity added is lower than the stoichiometrically required quantity of the precipitation agent. This has been explained by the Mg(OH)2 partical model. In order to interpret the experimental data obtained by the batch-settling tests a calculation of a continuous thickener was made by applying the Kynch theory. It was observed that at 100% precipitation the quantity of the precipitate obtained was 23.05 ?$kgh^{-1}$?, while that obtained at 80% precipitation was 52.69 ?$kgh^{-1}$?, which indicates a considerable increase in the thickner productive capacity. Thus, it could be seen that the settling rate of the magnesium hydroxide slurry was very important in computing the thickening area required.
Keywords: magnezijev hidroksid; morska voda; flokulanti; flokulacija; usedanje